India Nepal partnership and South Asian resurgence - Dharamdasani, M. D., 1947-; International Seminar on Perspectives of Indo-Nepal Relations (1999 : Centre for the Study of Nepal, Banaras Hindu University) (New Delhi : Kanishka Publishers, Distributors, 2000)
Contributed articles presented at the International Seminar on Perspectives of Indo-Nepal Relations organised by the Centre for the Study of Nepal, Banaras Hindu University in March 1999.
Includes bibliographical references and index.
Keywords: India -- Foreign relations -- Nepal -- Congresses; Nepal -- Foreign relations -- India -- Congresses; India -- Foreign relations -- 1947-1984 -- Congresses; India -- Foreign relations -- 1984- -- Congresses